Family Health Behavior Against Alleged Acute Respiratory Infections in Preschool Children - Hayyu Putri Utami; Farida Wahyu Ningtyias; Candra Bumi (Alliance oh Health Activists (AloHA), 2019)
Acute respiratory infections is the main cause of morbidity and mortality on children. The incidence of ARI in Indonesia is still high. Family health practice is one of the factors causing ARI. This study aims to analyze the effect of family health practice on suspected ARI in preschool children. This study uses a quantitative approach by type of observational research and cross sectional research design. This research was conducted in kindergarten in working area of Kedungrejo Muncar Health Center and conducted in August-September 2019. The samples of this study were 103 preschool children in a kindergarten in working area of Kedungrejo Muncar Health Center, Banyuwangi Regency, East Java Province. It used random sampling. The analytical method used was logistic regression analysis. The analysis results of this study was for family health behavior that had an affect the suspected ARI in preschool children practice, they were opening windows every morning and evening (p = 0.037), hand washing behavior (p = 0.014), behavior of not closing mouths and nose when coughing (p = 0.004). Family health behavior that did not have an influence on suspected ARI in preschool children, they were behavior of smokingg in the home by family or guests (p = 0.545), behavior of wearing masks when coughing or during a cold (p = 0.337), behavior of burning trash near the home (p = 0.955), the practice did not immediately bring the child to a health care facility if ARI was accompanied by fever (p = 0.378). Keywords: family health behavior; preschoolers; acute respiratory infections